Povečanje varnosti transfuzije krvi novorojenčkov z večkratno uporabo filtriranih krvnih komponent enega dajalca - Bizjak, Bojana (Zdravniški vestnik, 2004)
Background. As neonates are among the most frequent recipients of blood components, they are exposed to large numbers of blood donors. This, and particularly their immune immaturity, puts them at high risk of posttransfusion complications. When preparing blood components for neonates, we try to make the components as safe as possible, decreasing the neonate's exposition to a large number of blood donors. We wanted to know whether our attempts to reach this aim by applying filtration for all blood components, concentrated erythrocytes, fresh frozen plasma and thrombocyte concentrate was successful. The blood components were divided into small doses using the method of sterile connection and assuring the components of a single donor. Methods. Whole blood was filtered within 6 hours after withdrawal in the closed blood-bag system - in line filtration. Filtered concentrated erythrocytes and filtered fresh frozen plasma are thus obtained. Thrombocyte plasma is filtered on order. Using sterile connection, the bugs for further division of blood components are then connected to the bags with the individual blood components. Results. In the past year, 62 neonates received two or more blood components. They received a total of 383 transfusions, an average of 6.17 blood components per infant. Altogether, the neonates receivedthe blood components of 214 blood donors and were exposed to 3.45 donors on the average. The range of the number of donors, whose blood components were received by the infants, was between one and up to 24 donors, to which two were exposed. Conclusions. At our department we follow the recommendations of the European Council. All blood components for neonates are filtered, and from one donor if possible. We were extremely successful in decreasing the exposition of the neonates to large numbers of blood donors. Instead of those of 383 blood donors, the infants received the blood components of only 214 blood donors. The exposition was thus decreased by 55.9 %.
Keywords: Blood donors; Blood transfusion; Dojenček, novorojenček; Eritrociti; Erythrocytes; Infant, newborn; Krvodajalci; Plasma; Plazma; Thrombocytes; Transfuzija krvi; Trombociti